Cross sectional study of childhood obesity and prevalence of risk factors for cardiovascular disease and diabetes in children aged 11-13 - Brophy Sinead; Thomas Non; Rees Anwen; Knox Gareth; Williams Rhys (BMC, 2009)
Abstract Background Childhood obesity levels are rising with estimates suggesting that around one in three children in Western countries are overweight. People from lower socioeconomic status and ethnic minority backgrounds are at higher risk of obesity and subsequent CVD and diabetes. Within this study we examine the prevalence of risk factors for CVD and diabetes (obesity, hypercholesterolemia, hypertension) and examine factors associated with the presence of these risk factors in school children aged 11-13. Methods and design Participants will be recruited from schools across South Wales. Schools will be selected based on catchment area, recruiting those with high ethnic minority or deprived catchment areas. Data collection will take place during the PE lessons and on school premises. Data will include: anthropometrical variables (height, weight, waist, hip and neck circumferences, skinfold thickness at 4 sites), physiological variables (blood pressure and aerobic fitness (20 metre multi stage fitness test (20 MSFT)), diet (self-reported seven-day food diary), physical activity (Physical Activity Questionnire for Adolescents (PAQ-A), accelerometery) and blood tests (fasting glucose, insulin, lipids, fibrinogen (Fg), adiponectin (high molecular weight), C-reactive protein (CRP) and interleukin-6 (IL-6)). Deprivation at the school level will be measured via information on the number of children receiving free school meals. Townsend deprivation scores will be calculated based on the individual childs postcode and self assigned ethnicity for each participating child will be collected. It is anticipated 800 children will be recruited. Multilevel modeling will be used to examine shared and individual factors associated with obesity, stratified by ethnic background, deprivation level and school. Discussion This study is part of a larger project which includes interviews with older children regarding health behaviours and analysis of existing cohort studies (Millennium cohort study) for factors associated with childhood obesity. The project will contribute to the evidence base needed to develop multi-dimensional interventions for addressing childhood obesity.